Yemeni Houthi Blockade of Israeli Merchant Ships in the Red Sea and Its Impact on Regional and Global Stability - Munzilin, Khairul; Mahardhika, M. Anugrah Putra (The Indonesian Islamic Studies and International Relations Association (Insiera), 2024)
The Red Sea is a strategic region that connects the Middle East, Africa, and Asia, and is a vital trade and transportation route for the world. However, it has also witnessed conflicts and tensions between various actors, including Israel and the Yemeni Houthi. This research aims to analyze why the Yemeni Houthi blockade Israeli-bound merchant ships in the Red Sea, and how it impacts regional and global stability. This research uses a qualitative method with literature study techniques to obtain data from various sources, such as books, journals, reports, media, and official documents. The results showed that the blockade of Israeli merchant ships by the Yemeni Houthi in the Red Sea was motivated by political, economic, military, and ideological factors, relating to the conflict between Israel and the Yemeni Houthi, the Yemeni civil war, the Saudi-Iranian rivalry, and the United States' support for Israel. The blockade negatively impacts regional and global stability, as it creates insecurity, economic losses, humanitarian crises, and diplomatic obstacles between the actors involved.